The Effect of Adding Bee Pollen at Different Concentrations to Marshmallow Candy on Water Content, Water Activity, Texture, Color, Ash Content, Reducing Sugar, Antioxidant Activity, and Organoleptic Properties - Amertaningtyas, Dedes; Budiarti, Indi Rachmaning; Fatmala, Dina; Al Awwaly, Khothibul Umam; Evanuarini, Herly; Andriani, Ria Dewi; Hermanto, Feri Eko; Umam, Ahmad Khoirul (Journal of Agriprecision & Social Impact, 2026)
Marshmallow is one of the confectionery product that made from gelatin and sugar that have the weakness of lacking nutrients but favored by people of all ages. Bee pollen can be the one of natural addition that can enrich the nutrient in marshmallows. The aim of this study was to evaluate bee pollen addition with different concentrations reviewed from physicochemical and organoleptic test of marshmallows. Tresearch method used was a experimental using Complete Randomized Design (CRD) with 4 treatments and 5 replications. Four treatments were applied: P0 (without bee pollen addition), P1 (5%), P2 (10%), and P3 (15%). The study resulted significant differences (P<0.01) in water activity, texture, Lab color, ash content, reducing sugar, antioxidant activity, color, aroma, dan overall organoleptic acceptance, and no significant differences (P>0.05) in moisture content and organoleptic texture. The values resulted increased in moisture content (36.85-37.64%), color a* (0.14-3.38), color b* (25.39-33.27), ash content (0.806-2.404%), reducing sugar (0.372-6.677%), and decreased in antioxidant activity (92.96-503.92 mg/ml) and fluctuated in water activity (0.74-0.86), texture (0.68-1.16 N), and color L* (79.70-91.92). The results of the organoleptic test were still acceptable up to treatment P3. Overall, this study resulted the best results in treatment P3 with a bee pollen concentrations of 15% to increase the nutritional content of marshmallows.